2016
DOI: 10.1002/joc.4603
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends of downward surface global solar radiation over the Iberian Peninsula based on ERA‐40 reanalysis

Abstract: A climate study of the incidence of downward surface global solar radiation (SSRD) in the Iberian Peninsula (IP) based primarily on ERA-40 reanalysis is presented. NCEP/NCAR reanalysis and ground-based records from several Portuguese and Spanish stations have been also considered. The results show that reanalysis can capture a similar inter-annual variability as compared to ground-based observations, especially on a monthly basis, even though annual ERA-40 (NCEP/NCAR) values tend to underestimate (overestimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
3
5
1
Order By: Relevance
“…with an increase of global radiation at the surface. Based on observations and ERA-40 reanalysis, Perdigão et al (2016) confirmed the existence of these two distinct periods in Portugal, known as dimming and brightening, but with an earlier turning year than the one described in the literature, in particular over the south of Portugal. This latter study revealed an increasing trend of surface global radiation located in the south of Portugal, without a pronounced decrease before the 1980s, in the period 1964-1986. Before reaching the Earth's surface, incoming solar radiation is scattered, absorbed and reflected in the atmosphere.…”
Section: Accepted Manuscript 1 Introductionsupporting
confidence: 70%
“…with an increase of global radiation at the surface. Based on observations and ERA-40 reanalysis, Perdigão et al (2016) confirmed the existence of these two distinct periods in Portugal, known as dimming and brightening, but with an earlier turning year than the one described in the literature, in particular over the south of Portugal. This latter study revealed an increasing trend of surface global radiation located in the south of Portugal, without a pronounced decrease before the 1980s, in the period 1964-1986. Before reaching the Earth's surface, incoming solar radiation is scattered, absorbed and reflected in the atmosphere.…”
Section: Accepted Manuscript 1 Introductionsupporting
confidence: 70%
“…Similar significant increases were observed in the mean seasonal series, with the highest rate of increase during summer (6.5 Wm −2 decade -1 ). These results confirm the "brightening" phenomenon in Spain over the last decades, a pattern that was recently confirmed by Perdigao et al (2016) using reanalysis datasets.…”
Section: Changes In Solar Radiationsupporting
confidence: 88%
“…In Europe, the timing of the transition from dimming to brightening has been reported around the mid-1980s (e.g., Ohmura [13]; Norris and Wild [12]). On the other hand, Perdigao et al [14], using ERA-40 reanalysis, found that the transition occurred around the early 1970s over the Iberian Peninsula. Additionally, Kambezidis et al [18], using monthly re-analysis datasets from the Modern Era Retrospective-Analysis for Research and Applications, did not find a reversal from dimming to brightening during 1980s in the Mediterranean basin.…”
Section: Introductionmentioning
confidence: 99%
“…The various studies analyzing long-term records of surface radiation measurements suggest a widespread decrease in surface solar radiation between the 1950s and 1980s ("dimming", e.g., [6][7][8][9][10][11][12][13][14][15][16]), with a partial recovery after 1980 at many locations ("brightening", e.g., [8][9][10][11][12][13][14][15][16][17][18][19][20]). There are some indications for an "early brightening" in the first part of the 20th century (e.g., [10,13,21]).…”
Section: Introductionmentioning
confidence: 99%